2013
DOI: 10.7314/apjcp.2013.14.6.3663
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Antioxidant Status in Multiple Myeloma Patients: Effects of Therapy

Abstract: Background: Multiple myeloma is a malignant silent incurable plasma cell disorder. The present study aimed to assessed the activation of the oxidative stress pathway in afected patients Materials and Methods: Advanced oxidation protein products (AOPPs), malondialdehyde (MDA), adenosine deaminase (ADA), total antioxidant capacity (TAC) levels, glutathione, ascorbic acid (vitamin C), α-tocopherol (vitamin E) in addition to related enzymes glutathione peroxidase (GSH-Px), glutathione reductase (GSH-R) and superox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 23 publications
4
25
0
9
Order By: Relevance
“…Studies have declared the reduction in antioxidant capacity in patients with MM. This reduction in activity of antioxidants and involvement of oxidative stress in MM cancer are in line with the present study (39,40).…”
Section: Discussionsupporting
confidence: 78%
“…Studies have declared the reduction in antioxidant capacity in patients with MM. This reduction in activity of antioxidants and involvement of oxidative stress in MM cancer are in line with the present study (39,40).…”
Section: Discussionsupporting
confidence: 78%
“…A recent report showed that basal GSH levels are significantly elevated in MM patients after receiving therapy, which is consistent with our observation of resistant MM cell lines increasing GSH after L-PAM treatment. 56 Treatment with thiols (NAC and STS) antagonized the cytotoxic synergy of BSO+L-PAM, mimicking the effect of GSH as previously reported. 43, 57 The effect of NAC is independent of GSH because in the presence of BSO+L-PAM, NAC did not increase GSH levels.…”
Section: Discussionsupporting
confidence: 61%
“…High oxidative stress and DNA damage activity are increased, while the anti-oxidant enzyme levels are decreased in MM patients (Mehdi et al, 2013). Several free radical drugs, such as As 2 O 3 and ascorbic acid, have been used to treat MM, in which As 2 O 3 generates ROS while ascorbic acid serves as an anti-oxidant agent.…”
Section: Discussionmentioning
confidence: 99%